Tata Kelola Dana Desa Karang Taruna Desa Nakau, Kecamatan Talang Empat Kabupaten Bengkulu Tengah - Riandita, Nansi; Sarfah , Erma (Universitas Dehasen Bengkulu, 2021)
This research aims to examine the governance of village funds carried out by the Youth Organization of Nakau Village, Talang Empat District, Central Bengkulu Regency. The research method used is a qualitative approach with data collection techniques through in-depth interviews, observation, and documentation studies. The results showed that the governance of village funds by the Nakau Village Youth Organization has involved the active participation of all members of the Youth Organization and the local community in the process of planning, implementing, and monitoring the use of village funds. Nevertheless, there are some challenges faced, such as a lack of understanding of the mechanisms of village fund management and the expansion of the utilization of village funds for more inclusive programs. The implications of this study suggest the need for capacity building and transparency in village fund governance to ensure effectiveness and efficiency in the use of village funds for the sustainable development of Nakau Village community.